PEMANFAATAN AIR LAUT SEBAGAI SUMBER CADANGAN ENERGI LISTRIK - Adriani Adriani (Fakultas Teknik Universitas Muhammadiyah Makassar, 2020)
The development of science and technology is growing rapidly, as well as the development of knowledge about alternative energy. This study aims to analyze the design of the circuit form so as to produce electric current and to determine the operating flow of a series of seawater energy generating devices as a source of electrical energy reserves. The research was carried out by taking measurement data carried out by the Electrical Engineering laboratory. From the results of the measurement experiment the use of sea water explains that at one liter produces a voltage of 0.86 V, when using two liters produces a voltage of 1.85 V, when using three liters produces a voltage of 2.57 V. From the results of the research It was carried out that the voltage contained in 1 container of seawater was obtained 0.68 V, with the information of the lamp being off, and for 4 containers of sea water obtained a voltage of 3.87 V with a description of the lamp of life. This marine energy is used not only to turn on LED lights, but is used to power electricity in a narrow area or even in large areas. If this sea water energy can be developed in Indonesia, then the Indonesian state can save energy, because most of Indonesia's territory is water / sea. Energy sources derived from fossils at any time will soon be depleted. From the results of research conducted, it can be concluded that this sea water can be used as a source of renewable and environmentally friendly energy reserves.